Adopted children: a question of identity. Issue 3 (29th September 2015) - Mahmood, Samina; Visser, John
<x xml:space="preserve">Abstract</x> This article draws upon a study completed in a specific school in Bangalore where most children enter at the pre‐school level and continue till high school. While the particular children in the study constitute a small number – four – it was observed that questions of identity mainly arose when they started questioning the circumstances behind their adoption, were curious about their biological roots and searched for answers about their state of belonging. The findings in this study derive from observation of these children from the pre‐primary level to high school, supplemented by discussions, interviews and feedback from teachers who have worked with them, the parents of the adopted children, fieldwork and personal interactions, and show that sensitive handling and nurturing are essential in helping these children overcome the difficulties they experience.